Kurikulum Pendidikan Agama Islam: Konsep, Tujuan, dan Manfaat dalam Pengembangan Karakter Peserta Didik - Mardiah Astuti; Sania Hairunnisak; Tatia Desfika; Amanda Putri; Intan Oktaviani; Kenni Olandari; Gita Oktafryani; Sujenny Djeskyah (Educational Journal, 2026)
The Islamic Religious Education (PAI) curriculum holds a strategic position in Indonesia’s national education system as a guide for fostering moral, spiritual, and character-based development among students. This study aims to describe the concept, objectives, and benefits of the PAI curriculum in shaping individuals who are faithful, pious, and possess noble character. The research employs a qualitative approach through library research, analyzing various literature sources such as curriculum documents, academic books, and scholarly journals.The findings indicate that the PAI curriculum is systematically designed to integrate Islamic values with the development of intellectual, emotional, and spiritual intelligence. It serves to balance cognitive understanding and moral formation while preparing students to face the challenges of globalization with strong faith and ethical resilience. Furthermore, the PAI curriculum plays an essential role in cultivating Islamic character, strengthening moral integrity, and guiding educators in designing contextual and relevant learning processes.